2014
DOI: 10.1371/journal.pone.0090252
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Botulinum Neurotoxin A Subtypes 1-5 in Primary Rat Spinal Cord Cells

Abstract: Botulinum neurotoxins (BoNTs) are the most poisonous substances known and cause the severe disease botulism. BoNTs have also been remarkably effective as therapeutics in treating many neuronal and neuromuscular disorders. One of the hallmarks of BoNTs, particularly serotype A, is its long persistence of 2-6 months in patients at concentrations as low as fM or pM. The mechanisms for this persistence are currently unclear. In this study we determined the persistence of the BoNT/A subtypes 1 through 5 in primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
91
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(104 citation statements)
references
References 39 publications
11
91
1
1
Order By: Relevance
“…BoNT duration of action (Foran et al, 2003;McNutt et al, 2011;Whitemarsh et al, 2014), and the most recent studies reports a BoNT/A1 duration of action similar to that found in human autonomic nerve terminals, i.e. around one year.…”
Section: Gap 6 Duration Of Bont Paralysissupporting
confidence: 61%
“…BoNT duration of action (Foran et al, 2003;McNutt et al, 2011;Whitemarsh et al, 2014), and the most recent studies reports a BoNT/A1 duration of action similar to that found in human autonomic nerve terminals, i.e. around one year.…”
Section: Gap 6 Duration Of Bont Paralysissupporting
confidence: 61%
“…In this regard, the catalytic LC of BoNT/E (LCE), which also cleaves SNAP25 but causes only transient paralysis, is degraded relatively rapidly as a consequence of ubiquitination by the E3 ubiquitin ligase TRAF2 (12). In contrast, the LC of BoNT/A (LCA) is quite stable (12), which is consistent with the proteolytic activity of LCA remaining detectable in neuronal cultures for months (13,14). The activity of ubiquitin ligases toward proteins is highly specific; accordingly, despite 35% sequence identity between LCE and LCA, there is no evidence that TRAF2 ubiquitinates the highly stable LCA (12,15).…”
supporting
confidence: 59%
“…Restoration of synaptic function following BoNT/A intoxication is dependent upon, and thus correlated with, the recovery of full-length SNAP25 (13,35). A major factor contributing to the long duration of BoNT/A toxicity is the persistence of proteolytic activity of LCA, which continues to cleave newly synthesized SNAP25 (13,14,36). As a result, overexpression of WT SNAP25 is unable to restore exocytosis in BoNT/A intoxicated cells.…”
Section: Resultsmentioning
confidence: 99%
“…With the medical uses of BoNTs expanding and the recognition that botulinum neurotoxins are extremely useful to treat disorders unrelated to musculoskeletal spasticity, such as pain and inflammation (11), it is important to study the distinct characteristics of BoNT subtypes for new drug development. Our laboratory previously reported that BoNT/A2, -A3, -A4, and -A5 subtypes have different properties than the prototype BoNT/A1, including the elicitation of distinctive symptoms in mice (12)(13)(14)(15)(16). However, definitive studies of many BoNT subtypes are hindered by the lack of availability of most purified BoNT subtypes other than the primary BoNT for each serotype.…”
mentioning
confidence: 99%